Spoken errors of Malay language among Rohingya learners_a case study in Pelangi Kasih School - Senawi, Balqis; Nazir, Faridah; Jano, Zanariah (Kulliyyah of Languages & Management, IIUM Pagoh, 2021)
This study was conducted to identify the characteristics of spoken errors in Malay language and determine the factors of the errors made among the Rohingya students in the Pelangi Kasih School, a non-governmental organization run by the United Nations High Commissioner for Refugees (UNHCR), also known as the UN Refugee Agency. The methods employed were field experiments, interviews, and observation in Malay and Math classes. The findings yielded that the common errors made were in the usage of abbreviations, prepositions, code-mixing, affixes, and auxiliaries. The factors of committing the errors were attributed to three; ignorance, environmental and language interference. This study is beneficial for the UNCHR and school teachers in planning effective interventions to curb the problems of acquiring the Malay language among the refugee students.